Implementasi Pemberian Makanan Tambahan (PMT) Berbasis Pangan Lokal sebagai Intervensi Gizi Tepat bagi Anak Masalah Gizi Kurang di Desa Paga Kabupaten Sikka - Maria Susana Ine Nona Ringgi; Rosania Euthropia Brigita Conterius; Ariyanto Ayupir (Inovasi Kesehatan Global, 2025)
Nutritional problems in toddlers remain a major challenge in Indonesia, particularly in rural areas such as Paga Village, Sikka Regency. Nutritional problems are not only caused by a lack of nutritious food intake but are also exacerbated by the high incidence of infectious diseases, inadequate parenting, low public nutrition knowledge, limited access to health services, and low socioeconomic conditions. These factors directly and indirectly impact children's nutritional status. One intervention effort that can be implemented to address this problem is through the provision of locally-based food supplements (PMT), which aims to improve children's nutritional intake and encourage food independence and sustainable family nutritional security. This study aims to determine the effect of providing locally-based food supplements as a nutritional intervention on improving the nutritional status of toddlers experiencing malnutrition. The research method used was an observational analytic approach with a cross-sectional design approach. The sample in this study were toddlers with malnutrition status who received an intervention in the form of local food-based PMT. The results showed an improvement in nutritional status in toddlers after receiving PMT. A total of 46 toddlers who were initially malnourished experienced an improvement to normal nutritional status after the intervention. These results indicate that providing locally-based food supplements has a positive effect on the nutritional status of toddlers. In conclusion, local food-based PMT has proven effective as a nutritional intervention in improving the nutritional status of toddlers in Paga Village. Such programs need to be further developed and supported by various parties to reduce the prevalence of malnutrition in the community and strengthen local food self-sufficiency.